INVESTIGATION OF COUNTER-CURRENT FLOW LIMITATION FOR AIR-WATER IN A PWR HOT LEG EXPERIMENTAL LOOP FOR DIFFERENT GEOMETRY - Morghi, Youssef; Puente, Jesus; Mesquita, Amir; Baliza, Ana (International Journal of Engineering Technologies and Management Research, 2018)
Gas/liquid two-phase stratified flows in horizontal channels are frequently encountered in nuclear reactors, oil and gas pipelines, steam generators, refrigeration equipment, reflux condensers, packed columns, and heat pipes. The phenomenon known as countercurrent flow limitation, or flooding, is the limiting condition where the flow rates of neither the gas nor the liquid can be further increased without changing the flow pattern. This is the condition where the maximum air mass flow rate at which the down-flowing water mass flow rate is equal to the inlet water mass flow rate. This limiting condition, also known as onset of flooding, can occur in vertical or horizontal geometry. This work is a review of recent experimental investigations of countercurrent flow limitation (CCFL) for various hot-leg geometries of pressurized water reactors (PWRs). We compare results with those obtained from the Nuclear Technology Development Centre (CDTN) in 2005. Recent experimental results in the literature are in good agreement with the 2005 findings.